50 Age, histology and stage predict survival following adjuvant chemotherapy and radiation versus radiation alone in high-risk endometrial cancer: a study based on portec-3 criteria. (18th September 2019) - Casablanca, Y; Tian, C; Powell, M; Winterhoff, B; Chan, JK; Shriver, CD; Hamilton, CA; Maxwell, GL; Darcy, KM
Abstract : Objectives: Evaluate the impact of age, stage and histology on survival in high-risk endometrial cancer (EC) following treatment with chemotherapy and radiation (CTRT) vs. radiation alone (RT). Methods: Eligible patients were diagnosed with high-risk EC from 2004–2014 in the National Cancer Database based on PORTEC-3 criteria and treated with pelvic beam radiation and/or radioactive implants. The CTRT group also received multiple-agent chemotherapy. A propensity score approach controlled for differences in clinical factors. Survival was evaluated using weighted Kaplan-Meier and Cox model analyses with interaction testing. Results: There were 10, 009 women in the CTRT group and 10, 006 in the RT group. After balancing, a 4.9% improvement in 5-year survival and a 15% drop in the adjusted risk of death was observed following treatment with CTRT vs. RT ( P<0.0001 ). The survival benefit and reduction in the risk of death associated with CTRT vs. RT alone varied by age at diagnosis, stage and/or histology (figure 1, P<0.0001 for each interaction test) with the largest benefits at age ≥70 vs. <70 years old, with stage III vs. stage I/II disease and in serous/clear cell carcinoma vs. endometrioid carcinoma. CTRT was associated with a 20% increased risk of death in patients <70 years old with stage I/II endometrioid EC ( P<0.0001 ). Conclusions: Age, stage and histology merit consideration when selecting adjuvant therapy for high-risk EC patients based on a study in 20, 015 women.